SISTEM PEMANTAU KINERJA BERBASIS BALANCED SCORECARD: STUDI KASUS UKSW DALAM RANGKA MEWUJUDKAN RESEARCH UNIVERSITY - Tanone, Radius; Manongga, Danny; Tambotoh, Johan (BACA: Jurnal Dokumentasi dan Informasi, 2013)
Balanced scorecard is a concept that can be used as a performance monitoring system in an organization. Results of monitoring the performance of the organization by implementing a balanced scorecard to perform and produce measurement and monitoring from time to time. Satya Wacana Christian University wants to develop the concept of education in the direction of research in a Research University (RU). It is important for universities to create a strategy and carry out the action that RU can be realized. Application of the balanced scorecard use to see the vision and mission of the university to reach the next target should be done. As a leading university RU application of balanced scorecard need to be viewed from four perspectives: financial, customer, internal business processes, growth and learning. Based on the perspective that there is then established Key Performance Indicators (KPI) are selected according to the needs of SWCU realize RU. Performance monitoring system is used based Ms.excel. The implementation of the balanced scorecard and KPI development plans SWCU create RU in the resulting system performance monitor that can measure and monitor from time to time.